USER EXPERIENCE OF LMS UNISKA AS AN E-LEARNING PLATFORM WITH THE TAM METHOD - Agustyas, Ricky Dwi; Kurniawan, Erwin Hari; Sulistyanto, Irwan (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2024)
This study examines the user experience of the UNISKA LMS platform, implemented for blended learning at Kadiri Islamic University, utilizing the Technology Acceptance Model (TAM). The descriptive qualitative research, conducted with students and lecturers from the Department of English, collected data through observation, interviews, and documentation. Results show that the platform's perceived ease of use and usefulness significantly impact its acceptance. Users generally found the LMS beneficial for organizing study materials and enhancing engagement through multimedia integration. However, initial challenges included unfamiliarity with the system and technical issues like page maintenance problems and manual quiz input. Despite these issues, the platform facilitated a smooth transition from traditional to online learning environments, underscoring its potential to support modern educational practices. Improvements in system stability and feature simplicity are recommended to enhance user satisfaction and effectiveness. The findings contribute to understanding the practical application of LMS platforms in higher education, aligning with global trends in e-learning and ICT-based education models.